The Palgrave Handbook of Social Democracy in the European Union
XXII, 608 p.
Keywords: The nature of social democracy in the countries of the European Union is more significant and better understood than is indicated by the available literature. This thought-provoking handbook aims to redress this disparity by bringing together Political scientists from across Europe to provide a definitive collection on social democracy in the EU.